Culture Transmission Through the Gambang Semarang Traditional Arts Community in the Era of Globalization - Irfanda Rizki Harmono Sejati; Sunarto Sunarto; Udi Utomo; Eko Raharjo (Universitas Negeri Semarang, 2023)
Ethnic music cannot be separated from culture. Gambang Semarang is one of the traditional arts in the city of Semarang with various art communities that have become entrenched, from the young to the old. There are several Semarang gambang art communities that have their own uniqueness in preserving this traditional art. The transmission of gambang semarang music is a way of preserving, studying and passing on traditional arts so that they continue to exist and are increasingly recognized by the public. This study uses a qualitative method with a phenomenological approach. The results of this study show that there are several ways in which the transmission of the Semarang gambang gambang occurs in the current era of globalization, namely through the world of education, involving both educators and students, through digitalization and art exhibitions. The world of education certainly involves learning Semarang gambang music in schools, both elementary and tertiary levels. Transmission through digitization is of course inseparable from how we are friends and utilize technology for art preservation in the current era of globalization and holding art exhibitions so that the public is also actively involved in listening to and observing the gambang art of Semarang.